Origin: Encomium and Economic Important of Egungun Festival in Ogbomoso - Oyewale Peter Oluwaseun (Lakhomi Journal Scientific Journal of Culture, 2022)
Egungun among the Yoruba people as fondly called is a great and without exaggerations an impressive annual festival which impact on the economic activities could not be left out in the Yoruba land. Egungun festival is an historical event that brings together people from far and near to see the prove of evidence of the Yoruba strong religious beliefs and how it has been cleverly evolved to solved their problems and proficiency of the so-called Egungun, and overtime developed the potential substance of a sudden development in economic activities. The study revealed the origin of Egungun, How the festival draws people from far and near to partake in the festival, how it helps in the development of economic activities. The study derived its data from both Oral and and secondary sources. The study concluded that Egungun Festival has its incredible way of helping economic growth and is one of the last iota of culture left on Yoruba body of culture.